HUINCUL KIMVN. LOOKING AT HISTORY “FROM ABOVE” - Canales Tapia, Pedro (Revista de Historia Social y de las Mentalidades, 2024)
The following work is a proposition regional  historical, ethnographic character, which  covered the techniques and proposals  emanating from the oral history and memory  studies, provide a description of the life  situation of two elderly Mapuche. This story  shows, from orality of the subjects, the  connection and conflict decoupling between  life history and national history - hegemonic,  accounting and impoverished marginal seat  that the Mapuche population undergoes  structurally from loss its territory and  dismantle it in the nineteenth century. Thus, the story revolves Mapuche from  memory devices and their link with otherness,  from positions marked by the coloniality  of social relations among themselves and  with others / as. Rescue, then the historical  memory of two elderly Mapuche us into the  discussion about the ongoing construction of  ethnic identity and ethnicity deployment among  members of a particular group, there discourses  emerging from cultural, political and social  demands, which interpellate colonizing and  hegemonic society, from areas as diverse as the  ritual, the environment and the relationship man  - nature.
Keywords: Ethnicity; Historical memory; Mapuche history